(untitled) (American International Journal of Supply Chain Management, 2021)
This study examined the changing dynamics and the trend of rental value of housing build-up in the Ibeju-Lekki axis of Lagos State from 2003–2015. The study relies on secondary data obtained from records at Ibeju-Lekki Government administrative office further. From the records, it was revealed that there were fifty-five (55), fifty-nine (59), and thirty-nine (39) housing built-up areas respectively on the high, medium, and low densities. There were 3,411, 1745, and 549 housing built-up buildings in the identified housing built-up areas. Secondary data were analyzed using trend analysis. Results showed that there is slight difference in the rate and dynamics of increase of the housing built-up properties value during pre-privatization and post-privatization era in the study area.